2022
DOI: 10.1177/01976931221128608
|View full text |Cite
|
Sign up to set email alerts
|

The Eads earthwork: Implications for Hopewell ceremonialism

Abstract: Eads (33Ct750) is a recently discovered Hopewell hilltop earthwork, which encloses ∼10 ha above the Bares Run-O’Bannon Creek-Little Miami River confluence area. Eads falls within the interquartile size range of other Ohio Hopewell earthworks. Like the nearby Foster's enclosure, Eads is a sub-meter earthwork with a single pronounced east-to-west berm, > 70.0 m in length and > 5.0 m in height. The peak of promontory aligns with the center of the Goodnough-Brock mound (33Ct751) at a compass direction of 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…research, we have found numerous cultural burn layers and fire features (e.g., hearths) at these and other Hopewell sites. Indeed, we have excavated dozens of Hopewell and other ancient Native American sites and have only found anomalous peaks in Ir, Pt, microspherules, and meltglass in coeval strata and have never observed these peaks above or below the synchronously dated occupation layer [35][36][37][51][52][53][54][55][56]. This heterogenic distribution suggests a unique regional incident, such as the proposed airburst/impact event.…”
Section: Anthropogenic Burning As Possible Causationmentioning
confidence: 93%
“…research, we have found numerous cultural burn layers and fire features (e.g., hearths) at these and other Hopewell sites. Indeed, we have excavated dozens of Hopewell and other ancient Native American sites and have only found anomalous peaks in Ir, Pt, microspherules, and meltglass in coeval strata and have never observed these peaks above or below the synchronously dated occupation layer [35][36][37][51][52][53][54][55][56]. This heterogenic distribution suggests a unique regional incident, such as the proposed airburst/impact event.…”
Section: Anthropogenic Burning As Possible Causationmentioning
confidence: 93%